Successful outcomes of a monoamniotic twin pregnancy discordant for anencephaly - Swain, Sujata; Jena, Paresh Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Mono amniotic twin pregnancy discordant for anencephaly (MATDA) is a rare occurrence. 29-year-old primi gravida was diagnosed with mono amniotic twin one baby anencephaly and other baby normal at 14 weeks of gestation during NT scan. Patient was counselled regarding selective termination & expectant management outcomes. They wanted to continue the pregnancy with expectant management. She developed pregnancy induced hypertension around 30 weeks which was managed by oral labetolol. Caesarean section was performed at 36 weeks of gestation, with first baby normal & second baby Anencephaly. The normal newborn infant was discharged from SNCU without any complications. Expectant management of a mono amniotic twin gestation discordant for anencephaly diagnosed at the first trimester is associated with a favourable outcome for the unaffected foetus.